A Signal of Diligence? Student Work Experience and Later Employment Chances - Stijn Baert; Olivier Rotsaert; Dieter Verhaest; Eddy Omey (Institute for the Study of Labor (IZA), 2015)
We investigate the impact of student work experience on later hiring chances. To completely rule out potential endogeneity, we present a field experiment in which various forms of student work experience are randomly disclosed by more than 1000 fictitious graduates applying for jobs in Belgium. Theoretical mechanisms are investigated by estimating heterogeneous treatment effects by the relevance and timing of revealed student work experience. We find that neither form of student work experience enhances initial recruitment decisions. For a number of candidate subgroups (by education level and occupation type), even an adverse effect is found.
Keywords: J24; I21; D83; C93; 330; student employment; transitions in youth; human capital; signaling; randomised field experiments